Spatial distribution and shell utilization in three sympatric hermit crabs at non-consolidated sublittoral of estuarine-bay complex in São Vicente, São Paulo, Brazil - Sant'Anna, Bruno S. [UNESP]; Zangrande, Cilene M. [UNESP]; Reigada, Álvaro L.D. [UNESP]; Severino-Rodrigues, Evandro (My University, 2006)
The objective of the present study was to characterize the spatial distribution and shell utilization of three hermit crab species in the estuarine-bay complex of São Vicente, São Paulo State, Brazil. Monthly samples were done throughout two years, in the non-consolidated sub-littoral at the estuarine-bay complex. The environmental factors, such as temperature, salinity and depth, were measured every month. The three hermit crab species, Clibanarius vittatus, Loxopagurus loxochelis and Isocheles sawayai, were captured utilizing shells from six gastropods species; 92.7% of the hermit crabs utilized Stramonita haemastoma. The results suggest a strong correlation between hermit crabs spatial distribution and salinity, which was considered the main environmental factor limiting their distribution in the estuary. I. sawayai was the only species present in all transects sampled; C. vittatus was captured only in regions with low salinity and L. loxochelis occurred only in high salinity waters.
Keywords: Anomura; Clibanarius; Isocheles; Loxopaguros; crab; environmental factor; estuarine ecosystem; salinity; shell; spatial distribution; Brazil; Sao Paulo [Brazil]; South America; Clibanarius vittatus; Decapoda (Crustacea); Gastropoda; Loxopagurus loxochelis; Stramonita haemastoma